2010
DOI: 10.1111/j.1365-2133.2010.10057.x
|View full text |Cite
|
Sign up to set email alerts
|

Tomato paste rich in lycopene protects against cutaneous photodamage in humans in vivo: a randomized controlled trial

Abstract: Tomato paste containing lycopene provides protection against acute and potentially longer-term aspects of photodamage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 47 publications
4
122
0
1
Order By: Relevance
“…According to the results obtained in a previous study, lycopene naturally present in tomatoes and tomato paste protects against skin damage caused by solar radiation [142]. These are also the conclusions of the recently published study by Terao et al [143].…”
Section: Skin Damagesupporting
confidence: 77%
“…According to the results obtained in a previous study, lycopene naturally present in tomatoes and tomato paste protects against skin damage caused by solar radiation [142]. These are also the conclusions of the recently published study by Terao et al [143].…”
Section: Skin Damagesupporting
confidence: 77%
“…In this way, free radicals and oxidative stress have been recognized as important causes involved in aging and several physiological dysfunctions related to age (Meydani 2001;Mammucari and Rizzuto 2010). It is well-known that diet with high levels of antioxidants may enhance life quality (Reiter et al 2005;Rizwan et al 2011) In previous reports, we showed that tryptophan administration was able to reverse the age-related changes in the circulating levels of melatonin and serotonin in both mammals and ringdoves (Aparicio et al 2007;Paredes et al 2007;Sánchez et al 2008a, b). Also, we reported that diets enriched with tryptophan itself or with foodstuffs containing high levels of this amino acid were able to both consolidate sleep in newborns (Cubero et al 2005 and improve sleep and antioxidant capacity levels in young, middle-aged, and elderly individuals (Garrido et al 2009(Garrido et al , 2010.…”
Section: Introductionmentioning
confidence: 83%
“…In relation to lycopene, Stahl et al 27 demonstrated that daily consumption of 40 g of tomato extract (16 mg of lycopene) for ten weeks decreased the formation of erythema after exposure to solar radiation by 40%, while Aust et al 21 found an increase in the skin's ability to protect against UV radiation through the daily intake of approximately 10 mg of lycopene for twelve weeks. Furthermore, Rizwan et al 28 have demonstrated that the daily intake of 16 mg of lycopene for 12 weeks provides protection against acute skin damage caused by sun exposure and potentially also in the long term, due to the reduction of damage at the molecular/cellular level. Daily supplementation of 4 g of omega-3 (2.8 g of EPA and 1.2 g of DHA) for four weeks offered a small but significant effect on the increase in the minimum UVB dose required to cause erythema 29 .…”
Section: Discussionmentioning
confidence: 99%